A new flashover dynamic model of polluted HV insulators - Aydogmus, Z; Cebeci, M (Ieee-Inst Electrical Electronics Engineers Inc, 2004)
In this work, a model based on field criterion has been developed to represent the flashover phenomenon, which occurs due to surface pollution on high voltage insulators, under ac voltage. The values of potential and electric field on an insulator surface have been determined using the finite element method (FEM). The open model of the insulator has been used for calculating the resistance in series with the arc, in addition to the values of the leakage current and the arc gradient. As a new approach, this dynamic model uses Lagrange multipliers for the solution of the pollution flashover problem. Both the impedance and the electric field criterion have been used for the propagation of arc on the surface. A computer program called NFDM (new flashover dynamic model) has been developed to achieve this. The results obtained from the program have been compared with theoretical and experimental results of other researchers.
Keywords: dynamic model; pollution; flashover; FEM